Numerical simulation of three-dimensional free surface film flow over or around obstacles on an inclined plane - Baxter, Steven J. (2010)
Within the bearing chamber of a gas turbine aero-engine, lubrication of the shaft and other bearings is achieved by an oil film which may become significantly disturbed by interacting with a range of chamber geometries which protrude from the chamber wall. Minimizing these disturbances and preventing possible dry areas is crucial in optimizing a bearing chambers design. In addition, multiple obstructions may be located close to one another, resulting in a more complex disturbed film profile than by individual obstacles. Prediction of the disturbance of the film is an important aspect of bearing chamber design.